Igneous-metamorphic basement of Taquetrén Range, Patagonia, Argentina: A key locality for the reconstruction of the Paleozoic evolution of Patagonia. - Renda, Emiliano Manuel (2021)
Fil: Renda, Emiliano Manuel. CONICET-Universidad de Buenos Aires. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires (IGEBA), Intendente Güiraldes 2160, C1428EHA, Buenos Aires, Argentina.